Cloud computing: comparison of various features - Khan, Nawsher; Noraziah, Ahmad; Mustafa, Mat Deris; Elrasheed, Ismail (Springer, Berlin, Heidelberg, 2011)
Cloud computing is fundamentally altering the expectations for how and when computing, storage and networking resources should be allocated, managed, consume and allow users to utilize services globally. Due to the powerful computing and storage, high availability and security, easy accessibility and adaptability, reliable scalability and interoperability, cost and time effective cloud computing is the top needed for current fast growing business world. A client, organization or a trade that adopting emerging cloud environment can choose a well suitable infrastructure, platform, software and a network resource, for any business, where each one has some exclusive features. In this paper, we managed a comprehensive classification for describing cloud computing architecture. After this classification, easy to choose a specific cloud service out of several existing cloud computing services developed by various projects globally such as Amazon, Google, Microsoft, Sun, force.com etc. Using this survey results not only to identify similarities and differences of the various aspects of cloud computing, but also identifying some areas for further research.